Search for $$B_{(s)}^{*0}→ μ ^+μ ^-$$ B ( s ) ∗ 0 → μ + μ - in $$B_c^+→ π ^+μ ^+μ ^-$$ B c + → π + μ + μ - decays - LHCb Collaboration (European Physical Journal C: Particles and Fields)
Abstract A search for the very rare $$B^{*0}\rightarrow \mu ^+\mu ^-$$ B ∗ 0 → μ + μ - and $$B_{s}^{*0}\rightarrow \mu ^+\mu ^-$$ B s ∗ 0 → μ + μ - decays is conducted by analysing the $$B_c^+\rightarrow \pi ^+\mu ^+\mu ^-$$ B c + → π + μ + μ - process. The analysis uses proton-proton collision data collected with the LHCb detector between 2011 and 2018, corresponding to an integrated luminosity of 9 $$\text {\,fb}^{-1}$$ \,fb - 1 . The signal signatures correspond to simultaneous peaks in the $$\mu ^+\mu ^-$$ μ + μ - and $$\pi ^+\mu ^+\mu ^-$$ π + μ + μ - invariant masses. No evidence for an excess of events over background is observed for either signal decay mode. Upper limits at the $$90\%$$ 90 % confidence level are set on the branching fractions relative to that for $$B_c^+\rightarrow J\hspace{-1.66656pt}/\hspace{-1.111pt}\psi \pi ^+$$ B c + → J / ψ π + decays, $$\begin{aligned} \mathcal{R}_{B^{*0}(\mu ^+\mu ^-)\pi ^+/J\hspace{-1.66656pt}/\hspace{-1.111pt}\psi \pi ^+}&< 3.8\times 10^{-5}\ \text { and }\\ \mathcal{R}_{B_{s}^{*0}(\mu ^+\mu ^-)\pi ^+/J\hspace{-1.66656pt}/\hspace{-1.111pt}\psi \pi ^+}&< 5.0\times 10^{-5}. \end{aligned}$$ R B ∗ 0 ( μ + μ - ) π + / J / ψ π + < 3.8 × 10 - 5 and R B s ∗ 0 ( μ + μ - ) π + / J / ψ π + < 5.0 × 10 - 5 .